Pengaruh Brand Ambassador NCT Dream, E-WOM, dan Brand Image terhadap Purchase Intention pada Produk Mie Instan Lemonilo - Lukitaningsih, Ambar; Cahya, Agus Dwi; Octavian, Pingky (Universitas Proklamasi 45, 2024)
This research aims to determine the influence of the NCT Dream Ambassador brand, e-WOM, Brand image on Purchase Interest. This research uses four variables, namely brand ambassador, e-WOM, and brand image as independent variables, and purchase intention as the dependent variable. The population in this research are K-pop fans who live in the Special Region of Yogyakarta who are familiar with Lemonilo instant noodle products, with a sample of 100 respondents. The sampling method uses purposive sampling with data collection using a questionnaire. The research results show that the Ambassador brand, e-WOM, and Brand Image together (simultaneously) have a significant effect on intention to buy Lemonilo instant noodle products, the Ambassador brand does not have a significant effect on the intention to buy Lemonilo instant noodle products, e-WOM has a significant effect on Lemonilo instant noodle products, and brand image have a significant effect on purchase intentions for Lemonilo instant noodle products.